Thermographic response of non-structural concrete blocks made with industrial ash - Serrano Guzmán, María Fernanda (2020)
Ash is a waste product of different commercial activities. For the paper industry, the disposal of this residue, which results from the combustion of the coal used in the production process, represents a problem. For this reason, its use in the production of concrete blocks has been evaluated. The objective of this study is to compare the thermographic response of industrially-manufactured, non-structural concrete blocks that have been prepared with this ash. Additionally, the mechanical behavior of the blocks is compared when the ash is replaced on a percentage basis with cement. Likewise, substitutions of 10, 20, 30 and 40% of ash for cement were made for blocks that were prepared in accordance with quality control requirements of a concrete block plant. Specialized techniques such as X-ray diffraction and microscopy demonstrated the absence of toxic substances in the ash. The study revealed that thermal absorption capacity increases as more ash is used.